Influence of "El Niño" over the pluviometric regime in the Lake of Maracaibo basin - de Bautista, Susana; Morales, José; Romero, Euler (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This paper analyzes the influence of El Niño (ENSO) and El Anti Niño (NOENSO-La Niña) over the pluviometric regime on annual, monthly and daily extreme values in the south and west region of the Lake of Maracaibo basin, located at the north part of South America. It was observed moderate influence in the south part of the basin, with positive differences of 15% for the NOENSO years and negative differences of 10% in the ENSO years, this behavior is different from the Perú case, where ENSO increases precipitation. The bimodal sequence of monthly rain is not modified, but the second peak is greater in the NOENSO years. There were no significant differences for daily maximum extreme values.